2019
DOI: 10.1016/j.bbmt.2018.12.753
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Adenovirus Infection in Hematopoietic Stem Cell Transplantation Recipients: Findings from the AdVance Study

Abstract: Adenovirus (AdV) is an increasingly recognized threat to recipients of allogeneic hematopoietic stem cell transplantation (allo-HCT), particularly when infection is prolonged and unresolved. AdVance is the first multinational, multicenter study to evaluate the incidence of AdV infection in both pediatric and adult allo-HCT recipients across European transplantation centers. Medical records for patients undergoing first allo-HCT between January 2013 and September 2015 at 50 participating centers were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 32 publications
6
64
1
1
Order By: Relevance
“…Gavel et al [6] reported a case of a child with GvHD and subsequent bowel obstruction who had a history of CMV and ADV reactivation in the posttransplant period. ADV infection occurs in 32% of pediatric and 6% of adult transplant recipients [7]. Cidofovir is the most used antiviral therapy [8] in ADV reactivation, but it was not effective in our patient.…”
Section: Discussionmentioning
confidence: 64%
“…Gavel et al [6] reported a case of a child with GvHD and subsequent bowel obstruction who had a history of CMV and ADV reactivation in the posttransplant period. ADV infection occurs in 32% of pediatric and 6% of adult transplant recipients [7]. Cidofovir is the most used antiviral therapy [8] in ADV reactivation, but it was not effective in our patient.…”
Section: Discussionmentioning
confidence: 64%
“…ADV infections are not uncommon after pediatric kidney transplantation but seldom lead to clinical problems [43][44][45][46], whereas morbidity is much higher after stem cell transplantation [47]. There are only a few studies available concerning ADV-specific T cells after solid organ transplantation.…”
Section: Adenovirus-specific T Cellsmentioning
confidence: 99%
“…Although some patients remain asymptomatic and clear the virus spontaneously, others can present with rapid progression to fatal multiorgan failure. The incidence of AdV viremia following HSCT is higher in paediatric patients, with a significantly higher mortality for patients developing AdV disease [5]. Clinical manifestations include haemorrhagic enteritis or cystitis, pneumonia, hepatitis, encephalitis and multiorgan failure [6].…”
Section: Refractory Viral Infections Following Hsctmentioning
confidence: 99%